The Influence of Training, Competence, and Discipline on the Performance of Soldiers in Squadron-21/Multipurpose PUSPENERBAD - Gilang Bogie Utomo; Mochamad Vrans Romi (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
Puspenerbad is a combat mobility support unit for the Indonesian Army, which operates army-owned flight facilities, such as fixed wing and rotary aircraft. Puspenerbad has a strategic function in carrying out the tasks of Military Operations for War (OMP) and Military Operations Other Than War (OMSP). The personnel in it are more than 321 members with their respective specialization qualifications/ratings. Therefore, in supporting the main tasks as Airborne Flight personnel, they are required to have good and optimal performance. However, the problem with human resources for soldiers in Squadron-21/Multipurpose is the low achievement of soldier performance targets. The factors that influence performance are training, competence and work discipline. This study aims to determine training, competence and work discipline on performance in Squadron-21/Multipurpose Puspenerbad either partially or simultaneously. The research method used is quantitative research, the data collection technique used is a questionnaire and in analyzing the data using multiple regression analysis with the help of SPSS 26.0. Respondents in the study were 68 soldiers. The results of this study indicate that training, competence and work discipline have a positive effect on performance. While simultaneously training, competence and work discipline affect performance